Digital sound processing for music and multimedia - Kirk, Ross (Music technology series., 2013)
Provides an introduction to the nature, synthesis and transformation of sound which forms the basis of digital sound processing for music and multimedia. Background information in computer techniques is included so that you can write computer algorithms to realise new processes central to your own musical and sound processing ideas. Finally, material is inlcuded to explain the way in which people contribute to the development of new kinds of performance and composition systems. Key features of the book include: · Contents structured into free-standing parts for easy navigation · `Flow lines' to suggest alternative paths through the book, depending on the primary interest of the reader. · Practical examples are contained on a supporting website. Digital Sound Processing can be used by anyone, whether from an audio engineering, musical or music technology perspective. Digital sound processing in its various spheres - music technology, studio systems and multimedia - are witnessing the dawning of a new age. The opportunities for involvement in the expansion and development of sound transformation, musical performance and composition are unprecedented. The supporting website (www.york.ac.uk/inst/mustech/dspmm.htm) contains working examples of computer techniques, music synthesis and sound processing.